Pengaruh ekstrak daun binahong (Anredera cordifolia ) terhadap pemulihan siklus estrus mencit (Mus musculus) - Sari, Diana Novita; sumarmin, Ramadhan; Arsih, Fitri; Dwi Nugraha, Fitra Arya (Universitas Airlangga, 2021)
This study aimed to determine the effect of binahong (Anredera cordifolia) leaf extract on the recovery of the estrous cycle of mice (Mus musculus) which has been induced for the extension of the estrous cycle using angsana (Pterocarpus indicus) bark extract. In this study vaginal smear was performed daily at 10.00 WIB to determine the phase of the estrous cycle for 26 days. Mice were divided into 5 groups, each with 6 replicates. The treatments were T1 (positive control), T2 (negative control), T3 (0.8 mg/head/day), T4 (2.4 mg/head/day) and T5 (4 mg/head/day). The data obtained were processed using Analysis of Variance (ANOVA) and followed by the Duncan's New Multiple Range Test (DNMRT) at a 95% level of significance. The results showed that the angsana (Pterocarpus indicus) bark extract adminsitration (T2) lengthen (p <0.05) the estrous cycle of mice compared to those of normal mice (T1). The administration of binahong (Anredera cordifolia) leaf extract on T3 and T4 groups mice were followed by shorter (p <0.05) estrous cycle than those of T2, and it were not significantly different (p >0.05) compared to T1 group. However, the higher dose of binahong (Anredera cordifolia) leaf extract (T5) revealed the length of estrous cycle was not significantly different (p >0.05) compared to T2 group. It can be concluded that the administration of binahong leaf extract was able to recover the normal estrous cycle of mice.